Anchorless Transosseous Rotator Cuff Repair: A Technical Note - Matthew R. Cohn MD; Amar S. Vadhera BS; Harsh Singh MD; Johnathon McCormick MD; Morgan Wessels; Joseph A. Abboud MD; Nikhil N. Verma MD (SAGE Publishing, 2024)
Background: Transosseous rotator cuff repair provides robust fixation and broad footprint compression without the risk of foreign body reaction that may be seen with suture anchors. We present our technique for anchorless transosseous repair using a modern device to efficiently create bone tunnels and assist in suture passage. Indications: Tears of the supraspinatus tendon, with or without extension to the infraspinatus, in patients with acute or chronic tears, with good bone quality, and who fail appropriate nonoperative management. Technique: The beach-chair position with an articulating arm holder is preferred for this procedure. A glenohumeral diagnostic arthroscopy is performed, and intra-articular pathology is addressed as needed. The arthroscope is brought into the subacromial space, and a lateral viewing portal is established. A thorough bursectomy with or without acromioplasty is performed to attain visualization of the cuff. After the tear is identified, the tendon edges are debrided. It is critical to determine the tear pattern, the reduction maneuvers necessary, and the number of bone tunnels that are warranted. The desired location of the bone tunnel is marked with a pilot hole. The device is positioned over the pilot hole and a power drill is advanced through the lateral cortex. The device assists in creating a bone tunnel through the greater tuberosity and passes a nitinol loop through the tunnel. The loop is retrieved by the device and is brought to the lateral portal. Sutures are loaded into the loop and are brought through the bone tunnel. The sutures are then passed through the tendon using a curved retrograde suture passer in simple fashion and are tied to secure the tendon to the footprint. For larger tears, 2 or 3 tunnels may be used to widen the area for footprint compression. The specific configuration used will depend on the tear size, pattern, and surgeon preference. Results: Arthroscopic transosseous repairs have yielded promising results. Healing rates are comparable to anchor-based techniques, with the benefit of avoiding foreign bodies at the footprint. Discussion: Anchorless transosseous rotator cuff repair may be reproducibly performed with the use of a modern device for bone tunnel creation and suture passage. However, this technique should be used with caution in patients with osteoporosis or poor bone quality due to theoretical concerns of greater tuberosity fracture or suture pullout through the tunnels. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.